TEACHER PROFESSIONAL EDUCATION PROGRAM IN INDONESIA: BENEFIT AND CHALLENGE - Agustiani, Merie (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2024)
This paper reviews about benefit and challenges of teacher professional development in Indonesia. It also examines the types of Teacher Professional Program (known as Program Profesi Guru/PPG) which have been implemented by the government since the year of 2013.The teachers’ professional program both for in-service teachers and Pre- service teachers propose to enhance teacher professional development especially to improve their knowledge and competencies. For these reasons, the ultimate goal is by having professional teacher; it will lead to the students’ better achievement. Beside the benefits, this program also proposes many challenges. Lack of participants’ proficiency in using ICT, Instructors’ familiarity with the software, quality of the materials provided and availability of facilities are the challenges which are usually faced by in- service teachers. While for Pre service teachers, recruitment process is considered to be the main challenge since the policy government has evolved overtime, this condition causes many possibilities to use different regulation in the process of the recruitment over the year.